Analysis on the AAβ cryptosystem - Asbullah, Muhammad Asyraf; Kamel Ariffin, Muhammad Rezal (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
In this paper, we present three types of algebraic analysis upon the AAβ cryptosystem. First, we give the congruence relation in order to solve the AAβ equation. For the second and third analysis, we bring in the continued fraction’s method and the Coppersmith’s theorems, which presents several potential ways to retrieve the prime factor of p and q from the AAβ public keys or the plaintext m from the AAβ ciphertext, respectively. Thus, based on such analysis, suggestions are offered as a counter measure on how to secure the AAβ cryptosystem during key generation and encryption process.